2000
DOI: 10.1103/physrevc.61.067901
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase transport model for relativistic nuclear collisions

Abstract: To study heavy ion collisions at energies available from the Relativistic Heavy Ion Collider ͑RHIC͒, we have developed a multiphase transport model that includes both initial partonic and final hadronic interactions. Specifically, the Zhang's parton cascade ͑ZPC͒ model, which uses as input the parton distribution from the heavy ion jet interaction generator ͑HIJING͒ model, is extended to include the quark-gluon-to-hadronicmatter transition and also final-state hadronic interactions based on a relativistic tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
254
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(260 citation statements)
references
References 27 publications
2
254
1
Order By: Relevance
“…Section 6.3 presents the mass dependence of v sub n (p T ) which is followed by a discussion about the scaling properties of different flow harmonics in different centrality intervals. In section 6.5, two models, namely iEBE-VISHNU [49] and A Multi Phase Transport model (AMPT) [50][51][52], are compared with the experimental measurements. Note that the same data will be shown in different representations in the following sections to highlight the various physics implications of the measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Section 6.3 presents the mass dependence of v sub n (p T ) which is followed by a discussion about the scaling properties of different flow harmonics in different centrality intervals. In section 6.5, two models, namely iEBE-VISHNU [49] and A Multi Phase Transport model (AMPT) [50][51][52], are compared with the experimental measurements. Note that the same data will be shown in different representations in the following sections to highlight the various physics implications of the measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In particular in [23] it was shown that a hybrid model that couples the hydrodynamical expansion of the fireball to a hadronic cascade model describing the finalstate hadronic interactions is able to reproduce the basic features of the measurements at low values of p T . In parallel, various other models that incorporate a different description of the dynamical evolution of the system, such as AMPT, are also able to describe some of the main features of measurements of azimuthal anisotropy [50][51][52]. In this section, these two different theoretical approaches will be confronted with the experimental measurements.…”
Section: Comparison With Modelsmentioning
confidence: 99%
“…Final-state scatterings among hadrons are then modeled by a relativistic transport (ART) model [31]. The default AMPT model [20] has been quite successful in describing measured rapidity distributions of charge particles, particle to antiparticle ratios, and spectra of low transverse momentum pions and kaons [21] in heavy-ion collisions at the Super Proton Synchrotron (SPS) and RHIC. It has also been useful in understanding the production of J /ψ [25] and multistrange baryons [26] in these collisions.…”
Section: The Ampt Modelmentioning
confidence: 99%
“…The AMPT model [20,21,[25][26][27]] is a hybrid model that uses minijet partons from hard processes and strings from soft processes in the Heavy Ion Jet Interaction Generator (HIJING) model [28] as the initial conditions for modeling heavy-ion collisions at ultra-relativistic energies. The time evolution of resulting minijet partons is described by Zhang's parton cascade (ZPC) [29] model.…”
Section: The Ampt Modelmentioning
confidence: 99%
See 1 more Smart Citation